In control, optimistic, and resilient: Age-related effects of believing in a just world among adolescents. (March 2021) - Scholz, David; Strelan, Peter
Abstract: The Belief in a Just World (BJW) is an influential theory for explaining how individuals exert control in their lives. This is the first study to test, among adolescents ( N  = 1128), that control provides a mediating explanation for well-established positive relations between BJW-self and wellbeing outcomes. In addition, we examined whether age moderated the effect of BJW-self on control. In this cross-sectional study we found support for our five hypotheses: (1) BJW-self is positively associated with control, optimism, and resilience; (2) these relations occur indirectly through control; (3) increasing age dampens the positive effect of BJW-self on control such that (4) the indirect effects of BJW-self on optimism and resilience through control are accentuated among younger adolescents and (5) we replicated previous research showing that adolescents endorse BJW-self more than BJW-other and that the difference increases with age. Highlights: Adolescent age moderates positive effect of BJW-self on sense of control. Adolescent control is important for positive outcomes associated with BJW-self. Adolescents with strong BJW-self retain high levels of control regardless of age. Low BJW adolescents perceive less control when younger but more control when older.